Measuring Respiration Rate Based on Android - Shofiyah, Shofiyah; Wisana, I Dewa Gede Hari; Triwiyanto, Triwiyanto; Luthfiyah, Sari (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2019)
Abstract-Respiratory rate is the total number of breath or breathing cycle, which occurs every minute. Abnormal respiratory rate is a sensitive indicator for danger patients requiring medical treatment immediately. The objective of the study is to design a respiration rate monitor via an Android mobile phone. In this study, we used flex sensors to detect the respiration rate. The flex sensors were placed in the human stomach diaphragm which detects the changes in the human stomach diaphragm during breathing. The measurement results are displayed on the liquid crystal display (LCD) 2 x 16. The data will be sent via a Bluetooth connection to the android to display the values and graphs. The comparison between the design and standard showed that the maximum error is 4.69% while the minimum error is 1.52%. The average error for all measurement is 2.83%. It can be concluded that the tool wear is eligible because it is still below the minimum threshold of 10% error